Unraveling Structural Phase Transformation by Simultaneously Determining the Lattice Constants and Mismatch Angle in VO2/Al2O3 Epitaxial Thin Films - Liu, Yichao; Wang, Cangmin; Huang, Wenyu; Wang, Shaoting; Qiu, Huaili; Ge, Weifeng; Chen, Meixia; Zhang, Hui; Gu, Yueliang; Zhang, Xingmin; Li, Xiaolong; Gao, Xingyu; et al. (Frontiers in Materials, 2022)
As a prototype of a strongly correlated electron system, bulk vanadium dioxide (VO2) exhibits a large and reversible metal–insulator transition (MIT) near 340 K, concomitantly accompanied by a monoclinic–rutile structural phase transformation (SPT). In this study, we systematically investigated the SPT across the MIT in a (010)-VO2/(0001)-Al2O3 epitaxial thin film by simultaneously determining three lattice constants (a, b, and c) and the mismatch angle (Δβ) using high-resolution X-ray diffraction. The lattice constants a, b, and c were approximately 5.723, 4.521, and 5.393 Å, respectively, at room temperature, and the mismatch angle was approximately 124.02°. As the temperature increased, the lattice constants and mismatch angle did not change significantly until the temperature reached the MIT point. Then, a, b, and c suddenly increased to approximately 5.689 Å, 4.538 Å, and 5.411 Å, respectively, and retained this value up to nearly 90 ℃. However, the mismatch angle first slightly increased and then sharply decreased to 122.00°. Additionally, the lattice constants and mismatch angle were almost reproducible with decreasing temperature, except for hysteresis in the MIT region. These results verify that VO2 undergoes an MIT, simultaneously accompanied by SPT, in thicker films with small strain and weak substrate constraints, analogous to bulk VO2. This was further confirmed by in-situ varying-temperature Raman characterization. These findings provide insights into the SPT and reveal an angular parameter for judging the SPT in VO2 systems.